Pengaruh Penerapan Tata Kelola Perusahaan terhadap Profitabilitas Perbankan di Indonesia - Renaldi Putra; Yoselin Klen Elia Zakaria; Athalia Ariati Hidayat; Yang Elvi Adelina (Studi Akuntansi dan Keuangan Indonesia, 2019)
This research aims to analyze the impact of corporate governance implementation on profitability of bank in Indonesia. This research measured corporate governance with the score of ASEAN CG Scorecard index and TARIF index, while profitability was measured with ROA, ROE, and NIM ratio. Purposive sampling method was used and managed to gather twenty five samples of listed bank companies from 2011 to 2017. This research compared corporate governance principal of OECD and TARIF within ASEAN CG Scorecard. The result of this research concludes that the implementation of corporate governance does not have significant influence to company’s profitability. That is allegedly due to the lack of corporate governance implementation level based on ASEAN CG Scorecard. Banks tend to follow minimum standard of corporate governance by Financial Services Authority of Indonesia that only covered a small part of ASEAN CG Scorecard. The result indicates the need of more detail corporate governance measurement tool that is able to separate mandatory and voluntary disclosure.